Niat beli ulang mahasiswa terhadap kopi berkonsep coffee-to-go shop - Fibriyanti, Nur Afifah; Hukama, La Diadhan (Universitas Kristen Maranatha, 2021)
The competition for coffee shops in Indonesia is getting tighter, especially the coffee shop business with the coffee-to-go shop (take away) concept. The to-go coffee shop is a coffee shop that provides coffee drinks that are sold in packs that are ready to take (take away) so that they can be enjoyed in other places due to limited space. This study aims to analyze the effect of experiential marketing on repurchase intentions. The questionnaire in the study was distributed to 100 respondents with purposive sampling technique as a data collection technique. The findings in this study are that only the relate variable has a positive and significant effect on repurchase intention. Three other variables such as sensory, feel, and think have a positive but insignificant effect. While the act variable has a negative and insignificant effect. Thus, only a part of the experiential marketing dimension has an effect on the intention to repurchase students of the Faculty of Economics and Business, YARSI University.